New archaeological insights from petrographic analysis of ceramics from the Bocas del Toro Archipelago, Panama. (February 2018) - Marsaglia, Kathleen M.; Lawrence, John A.; Fitzpatrick, Scott M.; Wake, Thomas A.
Abstract: In this study, we conducted the first petrographic analysis of pottery from several Pre-Columbian archaeological sites located in Bocas del Toro province along the Caribbean coast of Panama. The fifty-four sherds examined in this study included surface finds collected from the sites of Red Frog (RF) and Punta Vieja Arriba (PVA) on Bastimentos Island, the Cerro Brujo (CB) site on the mainland, and excavated samples from Sitio Drago (SD), Isla Colon. Petrographic examination of sherd thin sections shows that different sandy materials (seven constituent natural and/or manually-added temper groups) were used in their production. Representative sherd compositions from each group were determined by petrographic point-counts (n = 200) using two matrix (silt and clay) and 14 mineral and rock fragment categories for sand grains. The sand in RF sherds is mainly fragments of mudstone, whereas sherds from the PVA and CB sites contain different proportions of sand-sized quartz, feldspar, dense minerals, and several varieties of volcanic lithic fragments. The latter components are constituents derived from local Panamanian geologic units, including one with pyroclastic temper that likely comes from a volcanically active region, such as the El Baru Volcano. Some of the archaeological sites (SD and PVA) have a greater variety of sherd compositional/temper groups than others, implying that people inhabiting these sites were actively engaged in acquiring materials and/or ceramics from multiple sources regionally. Highlights: Petrographic description of sherds from Pre-Columbian archaeological sites in Bocas del Toro Archipelago, Panama Seven temper compositional groups defined in 54 sherds derived from volcanic to plutonic to sedimentary geologic sources Some sites contain a wider variety of temper types.